Whose Islam? The Western University and Modern Islamic Thought in Indonesia - Jalaluddin, Mufti Labib (Islamic Studies Review, 2022)
For centuries, Islamic schools or madrasa have been the primary source of Muslim religious authority, with Indonesia no exception in this regard. For generations, Indonesia’s foremost Muslim leaders have received their Islamic education from Middle Eastern madrasas. In her book Whose Islam?, Megan Brankley Abbas challenges the notion of Middle Eastern centrality in Islamic education by arguing that Western universities has emerged as significant sites for the production of Islamic knowledge and Muslim religious authority in the last century. In her research, Abbas examines the far-reaching repercussions of this change for Muslim communities across the globe and for the future of Islamic studies as an academic discipline.